Intrapersonal communication among digital-age mothers on constructing postpartum body image - Citta, Givania Diwiya; Hidayat, Dasrun; Nurhadi, Zikri Fachrul; Rina, Nofha (Jurnal Kajian Komunikasi, 2024)
Background: The mom-body positivity movement is trending on social media to encourage mothers to find comfort in their new maternal bodies. In reality, many postpartum mothers experience antipathy for their body changes, and the way they deal with the stress of postpartum body image can impact their adaptation to the role of motherhood. Purpose: This study seeks to understand how intrapersonal communication within digital-age mothers constructs the meaning of postpartum body image. It is expected to motivate mothers to appreciate, accept, and love their maternal bodies. Methods: The research adopted the constructivist paradigm and a phenomenological study design, and the subjects were eight first-time mothers who had experienced childbirth within the past two years. Results: The study found that a mother’s journey to loving her postpartum body is diverse: some can instantly love their bodily changes, while others come to love their bodies later, after receiving positive affirmations from their closest circle. In addition, motherhood content on Instagram can provide virtual support to those who find it difficult to perceive their postpartum body image positively. Conclusion: Mothers are the key to happiness in the family. If they are unhappy, the baby is also unhappy. To create a healthy family, mothers require support from a healthy environment to construct a positive image of their postpartum bodies with minimal stress thus carrying out their maternal duties well. Implications: This study broadens mothers’ definition of beauty, further looks at postpartum mothers’ physical and mental well-being, and helps formulate better awareness and education on the meaning of postpartum body image at the individual, familial, and communal levels in Indonesia.